Tingkat Pengetahuan Masyarakat Desa Anjir Mambulau Tengah terhadap Penggunaan Antibiotik - Guntur Satrio Pratomo; Nuria Ayu Dewi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Medicine is all substances such as chemical, animal or vegetative in a possible dose that could heal, assuage or prevent the disease and its symptoms. Infectious disease is still the most of health society problem, especially in developing country. Antibiotics are chemical substances generated by microorganisms which have the ability to obstruct the growth or eliminate another microorganism. Antibiotics are the most widely used medicine for infectious which caused by bacteria. The accurate recipe and good consumption of antibiotics use will give well beneficial and effective for the patient. Otherwise, using antibiotics which not suitable for the instruction will conduct the decrease of the medicine function itself (antibiotics resistance), and could make new disease caused by the wrong application. Anjir Mambulau village is located in Province of Central Kalimantan, particularly the part of Kapuas Hilir district, Kapuas. These villagers mostly obtain the medicines from a small shop and consume it based on the experiences and family suggestions only. The purpose of this research is to know the knowledge level of Anjir Mambulau villagers about antibiotics use, using the descriptive method with the valid questionnaire, to the sample of the village's population by purposive sampling technique, the questionnaire contains any questions with semi-open way which made by the researchers that should be answered by the respondent. This research sourced from 309 respondents results that 35,5% villagers of AnjirMambulau have not the cognize of using antibiotics.